2016
DOI: 10.5194/aab-59-227-2016
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial control region diversity in Polish sheep breeds

Abstract: Abstract. The aim of the study was to determine the genetic variability of the Polish sheep breedsŚwiniarka, Wrzosówka, Pomorska, and Wielkopolska based on mitochondrial control region polymorphism. A comprehensive phylogenetic analysis and information about the genetic origin of the breeds were also obtained. The genetic variability of the breeds studied has been assessed based on the number of haplotypes, haplotype diversity, nucleotide diversity, the average number of nucleotide differences, the number of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 23 publications
4
5
0
Order By: Relevance
“…A comparison of the number of individual samples and the number of haplotypes ( Table-2 ) indicated that each breed had its haplotypes that could be due to the high diversity in local sheep breeds on Java Island and/or sampling strategy (collecting unrelated individuals) [ 31 ]. This is in line with the previous studies which states that several sheep breeds in Indonesia have high genetic diversity within [ 39 ] and between [ 50 ] populations. Unique patterns in the distribution of haplotypes could be attributed to the total reproductive isolation because of the harsh geographical structure of and unique husbandry practice on Java Island, that allow farmers to select animals with unique phenotypic characters associated with the adaptability to different ecological conditions [ 51 , 52 ].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…A comparison of the number of individual samples and the number of haplotypes ( Table-2 ) indicated that each breed had its haplotypes that could be due to the high diversity in local sheep breeds on Java Island and/or sampling strategy (collecting unrelated individuals) [ 31 ]. This is in line with the previous studies which states that several sheep breeds in Indonesia have high genetic diversity within [ 39 ] and between [ 50 ] populations. Unique patterns in the distribution of haplotypes could be attributed to the total reproductive isolation because of the harsh geographical structure of and unique husbandry practice on Java Island, that allow farmers to select animals with unique phenotypic characters associated with the adaptability to different ecological conditions [ 51 , 52 ].…”
Section: Discussionsupporting
confidence: 92%
“…[ 53 ] that Indonesian sheep have two Hap, namely, Hap A and B. Hap A is mainly represented in Asian breeds, whereas Hap B is found in high frequencies in European breeds [ 54 , 55 ]. This study is similar to observations on four Polish sheep breeds [ 39 ], eastern Ethiopia sheep [ 47 ], and Kail sheep [ 56 ] that form two Hap, namely, Hap A and B. All JFT, JTT, BTR, and WSB sheep are classified as Hap B.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Studies of many scientists on sheep from the Egyptian and Italian sheep breeds (Othman et al, 2015), Iranian sheep (Rafia and Tarang, 2016), Polish sheep (Koseniuk and Slota, 2016), Nepalese sheep (Gorkhali et al, 2015) were presented. The fragment of the D-loop region used in these studies varied from 76 to 721 b.p., with 55-132 polymorphic sites.…”
Section: Resultsmentioning
confidence: 99%